2020
DOI: 10.1371/journal.pone.0236869
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between marital status and incidence of type 2 diabetes mellitus in a Brazilian rural population: The Baependi Heart Study

Abstract: Many factors influence the incidence of type 2 diabetes mellitus (T2DM). Here, we investigated the associations between socio-demographic characteristics and familial history with the 5-year incidence of T2DM in a family-based study conducted in Brazil. T2DM was defined as baseline fasting blood glucose � 126 mg/dL or the use of any hypoglycaemic drug. We excluded individuals with T2DM at baseline or if they did not attend two examination cycles. After exclusions, we evaluated a sample of 1,125 participants, p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 36 publications
1
6
2
Order By: Relevance
“…Moreover, in Nigeria, couples tend to have regular feeding habits, mostly energy-dense foods such as cassava, yam, and rice, which may increase the risk of T2DM (Aladeniyi et al 2017). However, the present study is inconsistent with Haines et al (2018) andde Oliveira et al (2020) who reported a lower frequency of T2DM among married couples than singles.…”
Section: Discussioncontrasting
confidence: 99%
“…Moreover, in Nigeria, couples tend to have regular feeding habits, mostly energy-dense foods such as cassava, yam, and rice, which may increase the risk of T2DM (Aladeniyi et al 2017). However, the present study is inconsistent with Haines et al (2018) andde Oliveira et al (2020) who reported a lower frequency of T2DM among married couples than singles.…”
Section: Discussioncontrasting
confidence: 99%
“… 14 Finally, in a recent study based on a population in Brazil that included race and socioeconomic factors, only a combined covariate of divorce and the widowed was significantly related to the incidence of diabetes. 15 More generally, it is common in the morbidity, mortality and obesity literature for researchers to combine divorced/separated and widowed status into one covariate.…”
Section: Introductionmentioning
confidence: 99%
“…The current study found an association between social status and QoL in people with diabetes, with married individuals scoring higher than single, divorced, and widowed. According to a Brazilian study, people who stayed married despite gaining much more weight are significantly less likely to acquire diabetes than their divorced counterparts [ 20 ]. The quality of marriage was found to affect health-related QoL and disease adaptation in a survey conducted by the American Diabetes Association to assess the impact of marital status on glucose control in insulin-treated diabetics.…”
Section: Discussionmentioning
confidence: 99%